Coordinate-space Faddeev-Hahn-type approach to three-body charge-transfer reactions involving exotic particles - Sultanov, Renat A. [UNESP]; Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2000)
Low-energy muon-transfer cross sections and rates in collisions of muonic atoms with hydrogen isotopes are calculated using a six-state close-coupling approximation to coordinate-space Faddeev-Hahn-type equations. In the muonic case satisfactory results are obtained for all hydrogen isotopes and the experimentaly observed strong isotopic dependence of transfer rates is also reproduced. A comparison with results of other theoretical and available experimental works is presented. The present model also leads to good transfer cross sections in the well-understood problem of antihydrogen formation in antiproton-positronium collision. © 2000 The American Physical Society.